THE INFLUENCE OF TEMPERATURE AT CHARGING AND DISCHARGING THE LI-ION BATTERY (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
Li-Ion batteries are used as an energy storage element for various applications, from portable electronic devices to electric cars. The present study aims to explore how temperature variations affect the charging and discharging process of Li-Ion batteries, both theoretically and experimentally. For the experimental part, we made a data acquisition platform where we tested the behavior of a Li-Ion battery at different temperatures, starting from ambient temperature (22oC) and going in both directions, down to -20oC and up to +40oC. Both high and low temperatures can have more or less reversible adverse effects on battery capacity, charge rate, and overall performance. The subject is particularly important in optimising battery performance under different temperature conditions.
Keywords: Li-Ion battery; Thermal influence; Electric vehicles; Battery management system